CONSUMER PURCHASE INTENTION ON HALAL PACKAGED FOOD PRODUCTS: DOES HALAL LOGO AND INGREDIENTS MATTER? - Anon Khamwon; Nitipon Putatchote; Hasnizam Shaari; Norzieiriani Ahmad; Salniza Md. Salleh; Sany Sanuri Mohd Mokhtar; Rushami Zien Yusoff (Journal of Islamic, Social, Economics and Development, 2019)
The concept of halal is widely accepted in Muslim and non-Muslim countries. Halal conception is no longer perceived as a marketing jargon but it is a huge business. Manufacturers either from Muslim and non-Muslim countries had struggled to win Muslim and non-Muslim consumers to consume halal products of their brand. Halal not only lawful and permitted but covers the concepts of good, pure and wholesome. For halal packaged food product, packaging is consider as a first impression to lead consumer consumption. Halal logo and ingredients were highlighted as a potential stimulus. Due to in high demand and widely accepted, there is a tendency for misused of halal logo and ingredients. This study attempts to investigate whether halal logo and/or halal ingredients play a significant roles in stimulating consumer’s purchase intention of halal packaged food products. A mall-intercept approach in northern region of Malaysia among 110 respondents revealed that halal logo and halal ingredients significantly affect consumer’s decision. However, halal logo plays a crucial role in stimulating consumer’s purchase intention. Theoretical and practical implication is discussed at the end of the article.